2020
DOI: 10.1075/jslp.20003.tro
|View full text |Cite
|
Sign up to set email alerts
|

Second language comprehensibility as a dynamic construct

Abstract: Abstract This study examined longitudinal changes in second language (L2) interlocutors’ mutual comprehensibility ratings (perceived ease of understanding speech), targeting comprehensibility as a dynamic, time-varying, interaction-centered construct. In a repeated-measures, within-participants design, 20 pairs of L2 English university students from different language backgrounds engaged in three collab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 37 publications
(40 reference statements)
1
26
1
Order By: Relevance
“…To explore links between interlocutors’ comprehensibility and their perceived anxiety and collaborativeness, we revisited our dataset featuring paired interactions between L2 English speakers in three tasks, where the speakers carried out repeated assessments of themselves and each other (2.5 minutes apart) during 17 minutes of interaction. In our prior publication (Trofimovich et al, 2020), we tracked the speakers’ comprehensibility ratings across time, exploring whether the ratings converged or diverged over time and task. For this report, we analyzed previously unpublished data targeting the speakers’ self- and partner-specific ratings of anxiety and collaborativeness in relation to comprehensibility.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…To explore links between interlocutors’ comprehensibility and their perceived anxiety and collaborativeness, we revisited our dataset featuring paired interactions between L2 English speakers in three tasks, where the speakers carried out repeated assessments of themselves and each other (2.5 minutes apart) during 17 minutes of interaction. In our prior publication (Trofimovich et al, 2020), we tracked the speakers’ comprehensibility ratings across time, exploring whether the ratings converged or diverged over time and task. For this report, we analyzed previously unpublished data targeting the speakers’ self- and partner-specific ratings of anxiety and collaborativeness in relation to comprehensibility.…”
Section: The Present Studymentioning
confidence: 99%
“…What is missing from this body of work is a nuanced understanding of how comprehensibility unfolds over time in interactive scenarios, as speakers and listeners react and adapt to each other in real time. Recent work, which is compatible with dynamic views of language learning and use (de Bot et al, 2007), has begun to address this challenge, showing that comprehensibility is at least partially coconstructed (Trofimovich et al, 2020). Speakers and listeners appear to calibrate their speech to one another, resulting in a dynamic coupling of their comprehensibility.…”
Section: Introductionmentioning
confidence: 98%
“…Not surprisingly, participants in our studies provided comprehensibility ratings indicating that they could generally understand the speech of their conversation partners. In Trofimovich et al (2020), we found that the comprehensibility ratings were U-shaped over time. That is, listeners demonstrated high levels of understanding at the outset of the conversational tasks (i.e., after the first task) and again at the end of the third task.…”
Section: Dr O'brienmentioning
confidence: 83%
“…Building upon recent work in field (e.g., NAGLE; TROFIMOVICH; BERGERON, 2019), we conceived of "dynamic" to mean "varying over time" in our recent studies (NAGLE et al, 2021;TROFIMOVICH et al, 2020). Unlike other dynamic studies that investigate how ratings provided by someone external to a speech event change over time, we were interested in the extent to which both speakers in a dyadic interaction rate comprehensibility as well as their own and their partners' anxiety and collaborativeness in real time.…”
Section: Dr O'brienmentioning
confidence: 99%
“…accentedness (e.g., Bergeron & Trofimovich, 2017;O'Brien, 2014;Saito et al, 2017), and listener-based ratings have been used to understand different aspects of L2 speech learning, including how L2 speakers' pronunciation develops over time (Derwing & Munro, 2013;Nagle, 2018;Saito et al, 2018) and how their impressions of one another evolve throughout a communicative interaction (Trofimovich et al, 2020).…”
mentioning
confidence: 99%